REVIEW: FACTORS AFFECTING WAITING TIME FOR OUTPATIENT PRESCRIPTION DRUGS IN HOSPITALS - Eka Kristia Ayu Astuti; Ayun Sriatmi; Farid Agushybana (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2022)
Waiting is an activity which frequently causes uncomfortable feelings, particularly in health services. Patients who attend to health care facilities such as hospitals, are eager to receive good and quality health care system without having to wait for a long time. The quality of pharmaceutical services in hospitals influences the level of patient satisfaction with the services provided by pharmacy staff in drug services to patients. There are still numerous waiting times for outpatient prescription drug services in Indonesian hospitals which do not fulfill minimum service standards. Thus, the objective of this review articles is to determine the factors affecting the waiting time for outpatient prescription services at the hospital. This review was conducted by employing the literature review method with a sample size of 12 articles. The results acquired are several factors influencing the waiting time for outpatient drugs in hospitals encompassing: receiving prescriptions, providing etiquette, working on prescription drug concoctions, submitting drugs, facilities and infrastructure, human resources, hospital management information systems and standard operating procedures. Based on the complexity of the issue which was found in this review, the most dominant and influencing factors on the waiting time of outpatient drugs at the hospital are prescription reception, providing etiquette, preparation of prescription drugs, and submitting drugs.